Awangarda i tekst dromoskopowy - Kmiecik, Michalina (Teksty drugie, 2018)
This article aims to show how the avant-garde anthropological paradigm (based on notions of movement, progress, speed) relates to the philosopher Paul Virilio’s concept of dromoscopy. Virilio examines problems such as de-identification, loss of a stable subjectivity, the creation of an image of the human-projector that produces simulacra on the dashboard display. Kmiecik takes up these problems to develop the idea of the dromoscopic text, which, rather than thematizing movement, attempts to make it present in poetic language. To describe the transformation of avant-garde poetry, which strives from a fascination with the dromomaniacal subject towards dromoscopic discernment, Kmiecik uses two poems by Julian Przyboś as examples: Na uskrzydlonych kołach [On Winged Wheels] and Na kołach [On Wheels].